The role of data & synthesis centers in convergence research. Issue 1 (18th October 2019) - Pollock, Danielle; Allard, Suzie; Yan, An; Parker, Michelle
ABSTRACT: The convergence of scientific disciplines poses many challenges for data integration and management. As part of ongoing research into the role of data in new emerging research communities, we examined the perspective of synthesis center directors, professionals with expertise in supporting cross‐domain research using existing data to solve complex environmental challenges. Responses give insight into the roles data and synthesis centers play in the development of convergence research communities.